Connecting the spots: Leopard print fashion and Panthera pardus conservation - Good, C; Burnham, D; Moorhouse, T; Macdonald, D (Elsevier, 2021)
Leopard print is a proliferating fashion design with perpetual, cross–market appeal. But as demand for textiles replicating the leopard’s pattern soar, leopards themselves have disappeared from more than 75 % of the historic range. This study quantifies the fashion interest in leopard print to evaluate whether its popularity reflects an interest in wildlife, specifically in leopards or spotted cats, and whether this has contributed, or has the potential to contribute, to conservation. Global interest is documented and quantified by leveraging user–generated internet data (Google Trends Index), the traditional editorial media (Lexis Nexis), and social media (Instagram). The results suggest little correlation between interest in leopard print and interest (or concern) over leopards in the wild. In this context, conservation and fashion preferences may currently be linked only tenuously by most consumers, presenting a challenge, and potentially great opportunity, if they could be connected in ways making the relationship become mutually beneficial. As one way of achieving this, we conclude by proposing a wildlife royalties funding mechanism whereby the fashion print would benefit leopards through a payment scheme for rights of use for commercial purposes.